الوضعيات القانونية للموظف في التشريع الجزائري - طالب دنيا (جامعة المسيلة, 2024)
يتناول هذا البحث وصف وتحليل مختلف الوضعيات القانونية التي يكون فيها الموظف العام أثناء مساره المهني، وقد أقر المشرع الج ازئري هذه الوضعيات في تشريعاته الوظيفية والمتمثلة في وضعية القيام بالخدمة، وضعية االنتداب، وضعية خارج اإلطار، وضعية اإلحالة على االستيداع ووضعية الخدمة الوطنية. أين حاولت تحليل النظام القانوني لكل وضعية من خالل التعرف على مفهومها وحاالتها الخاصة ومختلف آثارها المترتبة عنها. كما بينت هذه الد ارسة أن اإلحالة على هذه الوضعيات يمكن أن يكون إما بطلب من اإلدارة أو من الموظف وذلك مع مراعاة اعتبار المصلحة العامة. وفي األخير يمكن القول أن هذه الوضعيات تعتبر وسيلة فعالة لضمان استمرار العمل اإلداري ولتحقيق التوازن بين الحياة المهنية للموظف وحقوقه السياسية واالجتماعية. الكلمات المفتاحية: الوضعيات القانونية، الموظف، اإلدارة العمومية. :Abstract This research addresses the description and analysis of various legal situations in which public employees find themselves during their professional career. The Algerian legislator has recognized these situations in its employment laws, which include the situation of active service, secondment, out-of-frame situation, referral to recall, and national service. The legal system of each situation has been analyzed by understanding its concept, specific cases, and the various consequences .resulting from it This study also illustrates that referral to these situations can be either at the request of the administration or the employee, while considering the public .interest In conclusion, these situations are considered an effective means to ensure the continuity of administrative work and to achieve a balance between the .professional life of the employee and their rights :Keywords .The legal situation, the employee, public administration
Keywords: الوضعيات القانونية، الموظف، اإلدارة العمومية.